Who is Replacing Sugar-Sweetened Beverages with Plain Water? Analyses of NHANES 2011–16 Data. (29th May 2020) - Rehm, Colin; Maillot, Matthieu; Vieux, Florent; Barrios, Pamela; Drewnowski, Adam
Abstract: Objectives: In the United States, replacing sugar-sweetened beverages (SSB) with plain drinking water is recommended via by numerous public health agencies and non-governmental organizations. While declines in SSB consumption in the US are well-documented, it is not clear if consumers are replacing SSBs with other beverages, namely plain drinking water. Methods: Beverage consumption data for 7453 children (4–18y) and 15, 263 adults (≥19y) came from two 24 h dietary recalls in three most recent cycles of the National Health and Nutrition Examination Survey (NHANES 2011–2016). Consumption trends for water intakes (in mL/d) from SSBs and from drinking water were analyzed by gender, age group, family income, and race/ethnicity. Results: Mean water intakes from SSBs declined from 322 mL/d to 262 mL/d (p-trend = 0.002) on average, whereas plain drinking water increased from 1011 mL/d to 1144 mL/d (p-trend = 0.0108). Statistically significant reductions in SSBs were observed only among men (-18%), younger participants (-26% in 4–8, -22% in 9–13, -33% in 14–19 and -30% in 20–30), those with lower incomes (family income-to-poverty ratio < 2.0), non-Hispanic whites and non-Hispanic black participants (p-trend < 0.05 for each). Within these population sub-groups, only non-Hispanic white participants, those with a family income to poverty ratio of 1–1.99, but not < 1.0, and children aged < 14y had a corresponding increase in plain water consumption. When examining types of water, non-Hispanic white participants replaced SSBs with tap water as opposed to bottled water, and the lower income group replaced SSBs with bottled water, as opposed to tap water. Conclusions: The expected replacement of SSBs with plain drinking water was not uniformly observed across socio-demographic group. Only non-Hispanic Whites and lower income groups replaced SSB with water, whereas teenagers (14–19y) and non-Hispanic black participants did not. Understanding how and if specific population sub-groups are replacing a declining food/beverage category with another category has important population health implications. Funding Sources: Analyses of publicly available federal NHANES databases were sponsored by PepsiCo Inc. and conducted by MS-Nutrition. The views expressed in this abstract are those of the authors and do not necessarily reflect the position or policy of PepsiCo, Inc.